Induction of Canonical Wnt Signaling by the Alarmins S100A8/A9 in Murine Knee Joints: Implications for Osteoarthritis. Issue 1 (January 2016) - van den Bosch, Martijn H.; Blom, Arjen B.; Schelbergen, Rik F. P.; Vogl, Thomas; Roth, Johannes P.; Slöetjes, Annet W.; van den Berg, Wim B.; van der Kraan, Peter M.; van Lent, Peter L. E. M.
Abstract : Objective: Both alarmins S100A8/A9 and canonical Wnt signaling have been found to play active roles in the development of experimental osteoarthritis (OA). However, what activates canonical Wnt signaling remains unknown. This study was undertaken to investigate whether S100A8 induces canonical Wnt signaling and whether S100 proteins exert their effects via activation of Wnt signaling. Methods: Expression of the genes for S100A8/A9 and Wnt signaling pathway members was measured in an experimental OA model. Selected Wnt signaling pathway members were overexpressed, and levels of S100A8/A9 were measured. Activation of canonical Wnt signaling was determined after injection of S100A8 into naive joints and induction of collagenase‐induced OA in S100A9‐deficient mice. Expression of Wnt signaling pathway members was tested in macrophages and fibroblasts after S100A8 stimulation. Canonical Wnt signaling was inhibited in vivo to determine if the effects of S100A8 injections were dependent on Wnt signaling. Results: The alarmins S100A8/A9 and members of the Wnt signaling pathway showed coinciding expression in synovial tissue in an experimental OA model. Synovial overexpression of selected Wnt signaling pathway members did not result in increased expression of S100 proteins. In contrast, intraarticular injection of S100A8 increased canonical Wnt signaling, whereas canonical Wnt signaling was decreased after induction of experimental OA in S100A9‐deficient mice. S100A8 stimulation of macrophages, but not fibroblasts, resulted in increased expression of canonical Wnt signaling members. Overexpression of Dkk‐1 to inhibit canonical Wnt signaling decreased the induction of matrix metalloproteinase 3, interleukin‐6, and macrophage inflammatory protein 1α after injection of S100A8. Conclusion: Our findings indicate that the alarmin S100A8 induces canonical Wnt signaling in macrophages and murine knee joints. The effects of S100A8 are partially dependent on activation of canonical Wnt signaling.